Household Spending And Income Inequality: Examining The Effects Of A Consumption–Based Tax In Ghana - Ocran, K.F. (University Of Ghana, 2023)
Over recent years, consumption taxes have increased government revenue and served as a fiscal stimulus tool in both developed and developing countries. Nevertheless, economic theory suggests that a broad-based consumption tax, such as value-added tax (VAT) is generally considered to be a regressive tax, implicitly affecting the economic welfare and standard of living of households, particularly in developing countries. Therefore, the objective of this study is to analyze the impact of VAT on household spending and income inequality in Ghana by incorporating Zivot–Andrews structural break unit root test in the series based on annual data that span the period 2000–2019. Importantly, the study employed the bootstrap autoregressive distributed lag modelling technique to examine the long-run and short-run relationship between the variables as well as the Toda–Yamamoto causality test is applied to ascertain the causal dynamics in the model. The empirical findings revealed that VAT can reduce household spending in the long-run but leaves no effect in the short-run. The elasticity of consumer spending with respect to VAT rate is inelastic in the long-run. Similarly, the VAT rate tends to be insignificant in the long-run while at the same time VAT rate exhibits a highly significant level and a negative effect on income inequality in the short-run. These results suggest that the impact of a change in VAT rate varies on household spending and income inequality. Based on these observations, the study recommends that fiscal authorities should focus on expanding the VAT base, as VAT tends to be less distortionary on consumer spending (inelastic) in the long-term, to maintain aggregate consumption and strengthen domestic resource mobilisation; on this account, better-targeted cash transfer programs should be financed using VAT revenue accrued.
MPhil. Economics Degree
Keywords: Household Spending; Income Inequality; Ghana; Consumption–Based Tax